2000
DOI: 10.1128/mcb.20.8.2915-2925.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response to Oncogenic Ras Involves Induction of the Cdk4 and Cdk6 Inhibitor p15INK4b

Abstract: The cell cycle inhibitor p15INK4b is frequently inactivated by homozygous deletion together with p16 INK4b , by itself, is able to stop cell transformation by Ras and other oncogenes such as Rgr (a new oncogene member of the Ral-GDS family, whose action is mediated through Ras). In fact, embryonic fibroblasts isolated from p15INK4b knockout mice are susceptible to transformation by the Ras or Rgr oncogene whereas wild-type embryonic fibroblasts are not. Similarly, p15INK4b -deficient mouse embryo fibroblasts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 71 publications
5
114
0
1
Order By: Relevance
“…Levels of expression of other CKIs, p27, p57, and p14 ARF , were also examined and found not to change. The mRNA levels of p15, another CKI implicated in senescence and Ras-induced arrest (Malumbres et al, 2000) were also found to be relatively unchanged. These results indicate that Rafinduced arrest of finite lifespan human epithelial cells does not require increased expression of the CKIs whose increased expression is associated with fibroblast senescence.…”
Section: Resultsmentioning
confidence: 89%
“…Levels of expression of other CKIs, p27, p57, and p14 ARF , were also examined and found not to change. The mRNA levels of p15, another CKI implicated in senescence and Ras-induced arrest (Malumbres et al, 2000) were also found to be relatively unchanged. These results indicate that Rafinduced arrest of finite lifespan human epithelial cells does not require increased expression of the CKIs whose increased expression is associated with fibroblast senescence.…”
Section: Resultsmentioning
confidence: 89%
“…As a CDK4/6 inhibitor, p15 INK4b overexpression is sufficient to induce a cellular senescent phenotype in cultured primary cells of early passages [24], as well as in human tumor cells [25]. Moreover, p15 INK4b up-regulation is responsible for the cellular senescence induced by oncogenic Ras and for the inhibition of cellular transformation [26]. The role of the CDK2 inhibitor p27 KIP1 in cellular senescence has been reported in some particular tumors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In cells that have lost tumor suppressors, their reconstitution can render the cells resistant to oncogenic stimuli. p16 Ink4a and p15 Ink4b were able to suppress cellular transformation by Ras in mouse embryo fibroblasts (MEFs) that had targeted homologous deletion at the respective locus (Serrano et al, 1995;Malumbres et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%